Contribution to the Rotifers and aquatic Tardigrada of Edgeøya (Svalbard) - Willem H. De Smet; E.A. Van Rompu; L. Beyens (Fauna Norvegica)
A preliminary account of the monogonont Rotifers and aquatic Tardigrada of Edgeøya is presented. Twenty-two taxa of Rotifera and nine taxa of Tardigrada are reported. All records are new for Edgeøya; six rotifer taxa and two tardigrada taxa are new for Svalbard.